Strategi Pemasaran Meningkatkan Hunian Tamu di VILLA DESAMUDA Seminyak - Ariana Sekardewi; Luh Komang Candra Dewi; I Putu Agus Suarsana Ariesta (Journal Research of Management, 2024)
This study aims to determine the competitive strategy implemented by the company. This research was conducted at Villa Desamuda Seminyak. The subjects in this study were department head managers and customers, totaling 14 people. This research was tested using SWOT analysis, namely by identifying various internal and external factors of the company, namely analysis of internal factors (strengths and weaknesses) and external factors (opportunities and threats) which were then formulated in the SWOT Diagram and SWOT Matrix. From the results of the analysis on the SWOT Diagram it appears that the position of Villa Desamuda Seminyak is located in Quadrant II which is described as a growth position, where internal factors total (2.68 – 2.97) therefore, appropriate strategies and results are needed to increase the guest house by increasing market development, market penetration and product development. As well as facing several opportunities and having various strengths that push to get these opportunities and it is recommended to carry out the SO, ST, WO, WT strategy. Strategies that can be implemented by companies are always issuing promotional packages and disseminating this information to anticipate more attractive offers from competitors, such as working with travel agents, updating information technology through digital marketing such as honeymoon packages, wedding packages, and promotions. meeting room.